Adaptation and implementation of clinical guidelines on maternal and newborn postnatal care in Iran: study protocol - Leila Abdoli Najmi; Sakineh Mohammad-Al; Shayesteh Jahanfar; Fatemeh abbasalizadeh; Haniyeh Salehi Poormehr; Mojgan Mirghafourvand (BMC, 2023)
Abstract Background According to World Health Organization (WHO), the postnatal care provision aims to provide care and treatment with the highest quality and the least intervention to obtain the best health and well-being for the family. The present study aims to adapt international guidelines for the clinical recommendations for the postpartum period and implement and determine its effectiveness. Methods/design This study will be done in two phases. In the first phase, international clinical guidelines for mother and newborn postnatal care will be adapted. The second phase is a randomized controlled trial in which the adapted guideline recommendations will be implemented, and maternal and neonatal outcomes will be measured. The ADAPTE method for adaptation of clinical guidelines, is usedg in the first phase. A systematic review was conducted in the databases and clinical guidelines related to postpartum care were extracted according to the inclusion criteria. The quality of clinical guidelines was evaluated using the AGREE-II tool. The WHO clinical guideline obtained the highest evaluation score and was chosen as the main guideline, and the NICE clinical guideline, with a second higher evaluation score, was also used to fill some gaps in the WHO guideline. Based on the pre-determined questions, recommendations will be sent to the relevant experts and stakeholders for their evaluation. After the external evaluation and the finalization of the recommendations, the postpartum clinical guideline will be compiled and used in the second phase of the study. In the second phase, 272 women in the immediate postnatal stage of the maternity and postpartum ward of Taleghani and AL-Zahra Hospitals in Tabriz will be assigned into the intervention (receiving care based on adapted guidline recommendations) and control (receiving routine hospital care) groups uing individual stratified block randomization. At 6 weeks after birth, we will complete the Edinburgh postnatal depression scale, postpartum specific anxiety scale and Barkin index of maternal functioning (to assess the primary outcomes), as well as a maternal health problems checklist, infant care behavior, and violence assessment questionnaires (to asses the seconadary outcomes). Further, the maternal health problems checklist and the Edinburgh postnatal depression scale will be completed in the second week after birth. The data will be analyzed using an independent t-test and ANCOVA. Discussion It is expected that the implementation of evidence-based clinical guidelines improves maternal and neonatal outcomes and experience of the postpartum period. The positive experience can also help to achieve Iran's population policies and the need to increase childbearing in the country. Trial registration: Iranian Registry of Clinical Trials (IRCT): IRCT20120718010324N76; Date of registration: 27/1/2023. URL: https://en.irct.ir/user/trial/66874/view ; Date of first registration: 27/3/2023.